Treatment technologies of palm oil mill effluent (POME)and olive mill wastewater (OMW): A brief review - Zhan Sheng, Lee; Sim Yee, Chin; Jun, Wei Lim; Thongthai, Witoon; Cheng, C. K. (Elsevier, 2019)
Attributable to the enormous population growth, tonnes of effluents are unavoidably generated throughout the agricultural activities. The inadequate effluents disposal induces perpetual contamination to the sea and river water sources, which has subsequently raised the public environmental concern. For that reason, the handling protocol of agricultural effluents was flagged up as an interest area for research. Despite the environmental hazards, agricultural effluents have the potential to be transformed from wastes into wealth via biological, physicochemical, thermochemical or a combination of processes thereof. The identical characteristics of palm oil mill effluent (POME)and olive mill wastewater (OMW)render the possibility of treating these wastes using the similar treatment method. Generally, biological treatment requires a longer process time compared to physicochemical and thermochemical technologies despite its easy and low-cost operation. Comparatively, physicochemical and thermochemical methods extend their potentiality in converting the agricultural effluents into higher value products more efficiently. This paper reviews the source and characteristics of both POME and OMW. Subsequently, a comparison of the current and alternative treatments for both effluents was done before the future perspectives of both effluents’ treatment are paved based on the well-being of the human, environment, and economic.